Eu, Tigre: a exuberância erótica em Georges Bataille - Rosa, Natália Rolim (2010)
This dissertation analyzes the thinking of Georges Bataille with the objective to investigate in his intempestivity the conception of eroticism. The complex movement that the author wages to develop this concept allows new possibilities to approach the nature/culture border, as well as animality and humanity concepts. In the introdution of The Eroctism the author announces to be in search of the Man in its totality, turning himself against the fragmentaries lines to pursuit the idea of a whole. This pursuance will be given by human passion and its only object, that implies in a tour upon the human spirit and its inner life. In the innerness of the being there is the encounter with the most overwhelming experiences, with the holy, the beauty, the horror and the passion. In the Baitaille's proposition there isn't borders between man and animal, mind and body, life and death; these instances constantly overflows one another and is in this intempestive movement that he sees the totality of the being. In this complex and unexpected field of human inner life, the being oversteps the limitrophes of the objective conscience into disconcerting experiences in which the conscience dissolves itself in the corporeal. The intent of this work it's to comprehend the totality that the batailliam thought seeks to reach in the inner experience consception by the means of problematization of the notions of eroctism, animality and humanity